Genetics of human Bardet–Biedl syndrome, an updates. Issue 1 (9th February 2016) - Khan, S.A.; Muhammad, N.; Khan, M.A.; Kamal, A.; Rehman, Z.U.; Khan, S.
Abstract : Bardet–Biedl syndrome (BBS) is an autosomal recessive multisystemic human genetic disorder characterized by six major defects including obesity, mental retardation, renal anomalies, polydactyly, retinal degeneration and hypogenitalism. In several cases of BBS, few other features such as metabolic defects, cardiovascular anomalies, speech deficits, hearing loss, hypertension, hepatic defects and high incidence of diabetes mellitus have been reported as well. The BBS displays extensive genetic heterogeneity. To date, 19 genes have been mapped on different chromosomes causing BBS phenotypes having varied mutational load of each BBS gene. In this review, we have discussed clinical spectrum and genetics of BBS. This report presents a concise overview of the current knowledge on clinical data and its molecular genetics progress upto date. Abstract :